2017
DOI: 10.5194/hess-21-5111-2017
|View full text |Cite
|
Sign up to set email alerts
|

Snow cover dynamics in Andean watersheds of Chile (32.0–39.5° S) during the years 2000–2016

Abstract: Abstract. Andean watersheds present important snowfall accumulation mainly during the winter, which melts during the spring and part of the summer. The effect of snowmelt on the water balance can be critical to sustain agriculture activities, hydropower generation, urban water supplies and wildlife. In Chile, 25 % of the territory between the region of Valparaiso and Araucanía comprises areas where snow precipitation occurs. As in many other difficult-to-access regions of the world, there is a lack of hydrolog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
1
15
0
2
Order By: Relevance
“…The monitoring of these water sources is a key activity for these regions due to the scarcity of water resources, aggravated by the growing water demand for agricultural, industrial, urban, and hydroelectric use [38][39][40][41]. Satellite snow monitoring [42] and artificial lakes for water storage [43] are two techniques that the Chilean government (DGA-General Directorate of Water) have implemented for water supply management.…”
Section: Study Areamentioning
confidence: 99%
“…The monitoring of these water sources is a key activity for these regions due to the scarcity of water resources, aggravated by the growing water demand for agricultural, industrial, urban, and hydroelectric use [38][39][40][41]. Satellite snow monitoring [42] and artificial lakes for water storage [43] are two techniques that the Chilean government (DGA-General Directorate of Water) have implemented for water supply management.…”
Section: Study Areamentioning
confidence: 99%
“…At mid-latitudes, Masiokas et al [17] analyzed the central region of the Andes and identified a positive correlation with warm phase of the El Niño/Southern Oscillation (ENSO), showing the importance of western air masses in the regulation of mountain snowfall. Between the northern and southern zone, Stehr et al [18] have studied spatiotemporal dynamics of snow cover over five Andean watersheds, detecting an important decline of snow cover. In the southern zone, [19] have studied the snowpack on the Northern Ice Field using satellite images and meteorological data.…”
Section: Introductionmentioning
confidence: 99%
“…En la Figura N° 3 queda manifiesta la acusada irregularidad interanual del proceso de innivación en la cuenca alta del Tormes debido a lo cual los ajustes lineales de las tres series no muestran ningún tipo de tendencia significativa, con valores de Rs (coeficiente de correlación de Spearman) próximos a 0. A escala global muy pocos análisis concluyen en la observación de tendencias estadísticamente significativas, incluso algunos resultados son contradictorios a la hora de establecer una tendencia general, debido en buena parte a la corta duración de las series y a la alta variabilidad interanual de los datos analizados (Maskey et al, 2011, Fayaz et al, 2013, Marchane et al, 2015, Li et al, 2017, Stehr & Aguayo, 2017, Verbyla et al, 2017. Además, en el estudio de las tendencias temporales, trabajos como el de Buisan et al (2016)…”
Section: Comparación De Las Imágenes Noaa Modis Y Spot Y Caracterizaunclassified
“…Finalmente, en América del Sur, la gran mayoría de las investigaciones se han desarrollado en Los Andes, como puede comprobarse en los resultados y discusión de una serie de trabajos publicados recientemente. Sproles et al (2016) desarrollaron un modelo hidrológico para estimar los caudales en el río Elqui en Chile, obteniendo los datos de fusión nival en Los Andes a partir de MODIS; Cornwell et al (2016) estudiaron el pico de fusión nival en Los Andes chilenos y argentinos, combinando los datos de MODIS con los de un modelo de balance de energía; por su parte Stehr & Aguayo (2017) analizaron la dinámica espacio-temporal del manto de nieve en 5 grandes cuencas en Los Andes chilenos en relación con el ENSO, observando una reducción no significativa de la cobertura nival en 3 de las 5 cuencas durante el período 2000-2016; finalmente, Saavedra et al (2018) también estudiaron la dinámica del manto de nieve en Los Andes durante el período 2000-2016, apreciando una reducción significativa del período de innivación y un ascenso altitudinal del límite del manto de nieve, especialmente en la vertiente oriental, que relacionaron con un aumento de las temperaturas y un descenso de las precipitaciones.…”
unclassified